2012
DOI: 10.1111/j.1365-2753.2012.01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Are health professionals’ perceptions of patient safety related to figures on safety incidents?

Abstract: This study indicates that the assessment of professionals' perceptions may be complementary to observed safety incidents, but not linked to an objective measure of patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…The definition of safety culture was lacking in two articles but they defined patient safety and patient safety incidents respectively [ 18 ]. There was one study where patient safety culture was defined as acceptance and actions of patient safety as the first priority in the organization [ 7 ] and four articles did not define safety culture [ 17 , 24 – 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of safety culture was lacking in two articles but they defined patient safety and patient safety incidents respectively [ 18 ]. There was one study where patient safety culture was defined as acceptance and actions of patient safety as the first priority in the organization [ 7 ] and four articles did not define safety culture [ 17 , 24 – 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another Dutch study identified that health care professionals who had a perception and understanding of patient safety had more incidents recorded [ 26 ]. All the health professionals surveyed felt that communication breakdown inside and outside the practice was a threat to patient safety and was associated with more incidents [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 presents data on the number and types of PSIs detected per 100 records per study. Five studies did not provide the data necessary for these calculations [ 15 , 28 , 34–36 ]. The mean number of PSIs per 100 records was 12.6 (SD = 7.21; range: 2.3–26.5).…”
Section: Resultsmentioning
confidence: 99%
“…Studies used similar rating scales to classify the harm resulting from PSIs, with severity categories ranging from ‘mild-moderate harm,’ ‘temporary harm,’ to ‘severe harm,’ ‘permanent harm’ and ‘patient death’ depending on the specific rating scale used. Four studies did not report severity of harm, and one study rated harm as ‘likely/unlikely’—these are excluded from Figure 2 [ 15 , 28 , 29 , 31 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Note. These figures do not total to 56 as six of the studies [13][14][15][16][17][18] included in the review employed two different types of patient safety assessment tools.…”
Section: Study Categorisationmentioning
confidence: 99%